EXAMINING THE ENVIRONMENTAL EFFICIENCY LEVEL OF ROAD TRANSPORT-INDUCED CO2 EMISSION: THE CASE OF INDONESIAN CITIES - Veby Renita, Ratu
Road transport has gradually become a crucial part of Indonesian urban transport system and plays a major role in future economic growth of Indonesia. However, road transport sector in urban areas is responsible for over 90% of the total fossilfuel consumption and is expected to increase transport CO2 emission by 12.9% per year. Therefore, to promote eco-efficient road transport, it is necessary not only to reduce the road transport CO2 emission, but also to enhance the environmental efficiency level of road transport-induced CO2 emission. Examining the environmental efficiency level of road transport activities by city scales and specify the policy implications is needed to provide valuable information not only about the current state of environmental sustainability of road transport sector, but also policy evaluation tools for improving environmental sustainability of road transport in Indonesian cities. Based on the stochastic cost frontier model with urban compactness as determinant of efficiency applied in this research, the results indicate that about 50% metropolitan cities considered to have poor environmental efficiency of road transport CO2 emission with the efficiency level less than 0.70. Meanwhile, all small cities have good environmental efficiency with the efficiency level more than 0.85. In evaluating the different policy implications, there are 13 (thirteen) policy scenarios introduced into the frontier model. The results shows that scenario combining policies related to the capital city relocation, urban density reduction, and transport supply upgrading is the most effective way to upgrade theii environmental efficiency level of road transport CO2 emission in Indonesian cities. In general, it is found that there are some opposite policy implications in metropolitan and big cities compared to medium and small cities. Thus, there is no a single formula of policy scenario that can be generalized to solve the problem of environmental inefficiency of transport CO2 emission in all cities.